2012
DOI: 10.1017/s0965539512000010
|View full text |Cite
|
Sign up to set email alerts
|

Review of Opioid Pca for Labour Analgesia

Abstract: The epidural route is currently the gold standard for labour analgesia, although it is not without serious consequences, especially when incorrect placement goes unrecognised. Intravascular, intrathecal and subdural placements have been reported to occur with incidences of 1 in 5000, 1 in 2900 and 1 in 4200 respectively. Until recent years there has not been a viable alternative to epidural analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Most studies were single-arm trials carried out between the 1940s and 1960s which makes the quality and relevance of their results questionable. Some authors concluded from these studies that pethidine shortened labour, others claimed it lengthened labour, and still others decided it did both, depending on which stage of labour it was given (Thomson & Hillier, 1994;Crafter, 2000;Hill & McMackin, 2012). A letter to the editor of the British Medical Journal in July 1947 conveys the most commonly held theory that had emerged by this time -that pethidine relaxed women enabling labour to progress.…”
Section: Pethidine Use To Shorten Labourmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were single-arm trials carried out between the 1940s and 1960s which makes the quality and relevance of their results questionable. Some authors concluded from these studies that pethidine shortened labour, others claimed it lengthened labour, and still others decided it did both, depending on which stage of labour it was given (Thomson & Hillier, 1994;Crafter, 2000;Hill & McMackin, 2012). A letter to the editor of the British Medical Journal in July 1947 conveys the most commonly held theory that had emerged by this time -that pethidine relaxed women enabling labour to progress.…”
Section: Pethidine Use To Shorten Labourmentioning
confidence: 99%
“…Pethidine readily crosses the placenta with maximum levels found in the baby's bloodstream between one and five hours following maternal administration (Tuckey, Prout & Wee, 2007). Fetal effects include reduced short term beat-to-beat variability of the fetal heart and neonatal effects include reduced Apgar scores, depressed muscle tone, respiratory effort, and sucking ability (Reynolds, 2010;Hill & McMackin, 2012). Other studies have raised additional concerns regarding the potential association between use of opioids in labour and development of neonatal drug dependency in later life, though this has not been proven (Nyberg, Allebeck, Eklund & Jacobson, 1993;El-Wahab & Robinson, 2011;Jacobson et al, 1990;Nyberg et al, 2000).…”
Section: Significant Fetal and Neonatal Concernsmentioning
confidence: 99%
“…Remifentanil seems to be beneficial for obstetric analgesia, and is already used in some countries. 9,15,175,184 Because of the unique pharmacokinetic properties, remifentanil has the potential to be the parenteral opioid of choice for women in labour.…”
Section: Future Perspectivesmentioning
confidence: 99%